Academic Senate Minutes 2011-11-10 - Academic Senate:::::::::
Revision to the Priority Registration Policy – First Reading completed. Resolution Regarding Endorsement of the CSU, San Bernardino Resolution Calling for Suspension of the CSU Online Initiative – First Reading completed.